MANAJEMEN SARANA DAN PRASARANA UNTUK MENINGKATKAN MUTU PENDIDIKAN - Sukatin, Sukatin (UIN Imam Bonjol Padang, 2020)
Improving the quality of education is a demand that must be met by every madrasa and schools in the era of globalization. Management of facilities and infrastructure is very important, because with the management of existing facilities and infrastructure in educational institutions will be maintained and their use clear. Management of the planning process, organizing, leadership and control of the efforts of members of the organization by using all organizational resources to achieve the stated goals. Management is a skill to move and control others to achieve predetermined goals. Educational facilities for all equipment, ingredient, and furniture that is directly used in the education process at school. Educational infrastructure is related to all basic equipment that indirectly supports the implementation of the learning process in schools. The emphasis on this understanding is on its nature, the means are direct and the infrastructure is not direct in supporting the learning process. The Head of Madrasah and also representatives of the Facilities and Infrastructure sector have done a good planning, but still there are things that have not been maximized from the plan, in terms of organization, mobilization has been done but in madrasas still less administration staff, and supervision has also been carried out well, while the obstacles faced are lack of infrastructure, lack of maintenance of facilities and infrastructure, funding and planning issues have not been maximized and lack of administrative staff. All managers of educational institutions should pay serious and monitored attention to the management of educational facilities and infrastructure, because educational facilities and means is one of the determining factors for the formation of an effective and efficient quality of education.